Self-supporting hierarchical porous PtAg alloy nanotubular aerogels as highly active and durable electrocatalysts - Liu, Wei; Haubold, Danny; Rutkowski, Bogdan; Oschatz, Martin; Huebner, Rene; Werheid, Matthias; Ziegler, Christoph; Sonntag, Luisa; Liu, Shaohua; Zheng, Zhikun; Herrmann, Anne-Kristin; Geiger, Dorin; et al. (Chemistry of Materials, 2016)
Developing electrocatalysts with low cost, high activity, and good durability is urgently demanded for the wide commercialization of fuel cells. By taking advantage of nanostructure engineering, we fabricated PtAg nanotubular aerogels (NTAGs) with high electrocatalytic activity and good durability via a simple galvanic replacement reaction between the in situ spontaneously gelated Ag hydrogel and the Pt precursor. The PtAg NTAGs have hierarchical porous network features with primary networks and pores from the interconnected nanotubes of the aerogel and secondary networks and pores from the interconnected thin nanowires on the nanotube surface, and they show very high porosities and large specific surface areas. Due to the unique structure, the PtAg NTAGs exhibit greatly enhanced electrocatalytic activity toward formic acid oxidation, reaching 19 times higher metal-based mass current density as compared to the commercial Pt black. Furthermore, the PtAg NTAGs show outstanding structural stability and electrochemical durability during the electrocatalysis. Noble metal-based NTAGs are promising candidates for applications in electrocatalysis not only for fuel cells, but also for other energy-related systems.
CRIS-Team Scopus Importer:2023-03-20